Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Tanjung Jabung Barat - Ubaidillah Ubaidillah (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study is to find out and describe the implementation of work motivation, work discipline and employee performance at the Regional Secretariat of Tanjung Jabung Barat Regency, as well as to find out how the influence of motivation and work discipline simultaneously and partially on employee performance within the Regional Secretariat of Tanjung Jabung Barat Regency. Research methods used are qualitative descriptive analysis methods and quantitative descriptive analysis methods, the type of data used is primary data with questionnaire questionnaires. The analysis method used linear regression analysis is simple. This study used a population of 62 respondents. Hypothesis testing was performed using a t-test, with a significant (Î±) 5%. Data analysis using statistical data management software namely SPSS 22.00 for windows.